CASE REPORT OCULAR MANIFESTATIONS IN A HIV POSITIVE AND SYPHILIS CO-INFECTION IN A 41 YEAR OLD MALE IN ALBANIA - Belshi, Amarildo (European Scientific Journal, ESJ, 2015)
The incidence of HIV in Albania has increased over the last decade, particularly among men who have sex with men. The ocular involvement is a clinical manifestation of HIV. Syphilis is a sexual infection disease that in this increased in the last 10 years. A co-infection of HIV and syphilis appears to increase the risk of ocular manifestation. The ocular manifestation of the patients with a co infection HIV-Syphilis will present with unexplained visual complaint. I am presenting a case of an ocular syphilis in a patient HIV positive presented in the department of Ophthalmology in Mother Teresa Hospital.